Serum Prolactin in Diagnosis of Epileptic Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The results of studies in databases and references concerning serum prolactin levels (PRL) in patients with suspected seizures were rated for quality and analyzed by members of the Therapeutics Subcommittee of the American Academy of Neurology.